Populist strategies in African democracies - Danielle Resnick (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Drawing on insights from Latin America, this paper examines the factors that contributed to the use of populist strategies by political parties during recent presidential elections in Kenya, South Africa, and Zambia. Specifically, the paper argues that the nature of party competition in Africa, combined with rapid urbanization and informalization of the labour force, provided a niche for populist leaders to espouse a message relevant to the region's growing urban poor. Simultaneously, such leaders employed ethno-linguistic appeals to mobilize a segment of rural voters who could form a minimum winning coalition in concert with the urban poor and thereby deliver sizeable electoral victories. While such strategies are similar to those used by Latin American populists, the paper highlights key contrasts as well. By combining cross-regional and sub-national perspectives, this paper therefore aims to contribute to a better understanding of how demographic and socioeconomic changes in Africa intersect with voting behaviour and political party development.
Keywords: O15; O17; O18; R11; 330; Africa; democratization; political parties; populism; urbanization; voting behaviour